The Implementation of PBL Model on Student Learning Outcomes in the Concept of Life Organizational Systems - Sri Amelia A. Sidiki; Tirtawaty Abdjul; Chairunnisah J. Lamangantjo; Trisnawaty Junus Buhungo; Frida Maryati Yusuf; I Made Hermanto (Postgraduate, University of Mataram, 2024)
This research aims to determine the effect of the Problem Based Learning (PBL) model on student learning outcomes in the concept of Life Organization Systems. This research is experimental research, with the research design used being a one group pretest-posttest design. The sampling technique used in this research was the total sampling technique. The population in this study was all class VII of SMP Negeri 3 Biluhu for the 2024/2025 academic year. The sample in this study consisted of 3 classes, namely the experimental class, the replication 1, and the replication 2, The experimental and replication classes were determined randomly. Research data was collected using test techniques, then the data was analyzed using descriptive statistics, which include normality tests, homogeneity tests, hypothesis tests, and n-gain analysis. The results obtained for the concept of Life Organization Systems using the PBL model through hypothesis testing where for the Tcount in the experimental class was 2.42; replication 1 was 2.32; replication 2 was 2.29, and the Ttable for experimental class was 2.14; replication 1 was 2.18; replication 2 was 2.16. It can be concluded that the hypothesis testing in each class is that the Tcount is greater than the Ttable. Thus, the implementation of PBL model has an effect on student learning outcomes in the concept of Life Organization Systems.